2017
DOI: 10.14214/sf.7749
|View full text |Cite
|
Sign up to set email alerts
|

Defoliation of <i>Tilia cordata</i> trees associated with <i>Apiognomonia errabunda</i> infection in Finland

Abstract: Highlights• Defoliation of Tilia cordata was investigated by fungal isolation from symptomatic leaf petioles and ITS sequence determination.• The disease symptoms were associated with the presence of Apiognomonia errabunda.• We report the first nucleotide sequences of A. errabunda from the Nordic countries. AbstractWe investigated the causative agent of a disease outbreak affecting small-leaved limes (Tilia cordata Mill.) and resulting in darkening of the leaf petioles and excessive defoliation during summer 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Perhaps, a significant asymmetry disrupted normal leaf functioning, and such leaves were eliminated by natural selection. It was reported that woody plants, including B. pendula and T. codata, lost some amount of leaves in summer [64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, a significant asymmetry disrupted normal leaf functioning, and such leaves were eliminated by natural selection. It was reported that woody plants, including B. pendula and T. codata, lost some amount of leaves in summer [64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%